Social media: engaging language learning - Mohd Sukri, Hanna Insyirah; Mustapha, Liyana; Othman, Moomala; Aralas, Dalia; Ismail, Lilliati (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
Most of youth nowadays have a problem of failing to perceive learning English as important as learning other subjects and therefore, slowly losing interest to get engaged in English lessons. Since Instagram, Twitter and other social media have been the main medium for them to express and share their ideas, this paper will discuss how the usage of social media helps in engaging language learners to use the target language in informal contexts. Today, teachers started to realize that some of these internet tools such as Facebook, Instagram, Email, and others are very useful in promoting language skills among students in schools. However, it cannot be assumed that students know the values of these tools in promoting their language learning. This paper will specifically look at Twitter and Instagram, the two major platforms of social media that are widely used among youth nowadays and adopt these mediums as the main agent of engagement for students in using the target language. Thus, instead of teachers looking at the negative side of social media, they should use it in class as a channel for language learning and teaching and direct students to realize social network as a catalyst to improve their English.